Penyusunan Leksikon Sensori sebagai Dasar Pengembangan Standar Mutu Sensori Teh Hitam Indonesia - Cecilia, Cory; Adawiyah, Dede Robiatul; Hunaefi , Dase (Jurnal Teknologi dan Industri Pangan, 2026)
The quality assessment of black tea infusion in Indonesia is currently relies on general and less specific sensory evaluations. This study aimed to develop a sensory lexicon specifically for Indonesian black tea infusion, which will include clear definitions and reference standards for each attribute. The lexicon was constructed through expert panelist interviews and focus group discussions (FGD) involving trained panelists who had passed a selection process based on basic taste and aroma identification and triangle test. A total of 30 black tea samples were evaluated in three FGD sessions, each involving at least six panelists. The study identified sensory attributes categorized into six main groups: appearance, aroma, flavor, taste, aftertaste, and mouthfeel. The lexicon includes both desirable quality attributes and defect indicators that reflect a decline in product quality. Each attribute was accompanied by a definition and a reference standard with intensity levels based on a 0–15 scale. This sensory lexicon provides a foundation for developing of a more objective, systematic, and measurable sensory quality standard for Indonesian black tea.